Caracterização de cultivares de cafeeiros resistentes à ferrugem submetidas à poda tipo esqueletamento - Reis, Estevam Antônio Chagas (2016)
The use of techniques with the aim of improving conventional methods for coffee selection is of great importance for the development of national coffee production. These techniques, such as framework pruning, favor the identification of more productive cultivars, responsive to management techniques. Thus, we aimed at evaluating the anatomical, physiological and agronomic traits, as well as the relation between them, in coffee cultivars originated from germplasm supposedly resistant to rust, and its response to framework pruning. The experiment was installed in an experimental area of the Deparment of Agriculture, coffee culture sector of the Universidade Federal de Lavras, using a randomized blocks design, with three replicates, in spacings of 3.5 x 0.7 m and plots of 12 plants. We evaluated 25 coffee cultivars, with 23 originated from germplasm supposedly resistant to rust and 2 commercial cultivars considered susceptible. We analyzed density and stomata functionality; number and diameter of the xylem vessels; thickness of the phloem, adaxial cuticle, adaxial and abaxial epidermis, palisade and spongy parenchyma, mesophile and limbus; length of the plagiotropic branch and number of knots; net photosynthetic rate; transpiratory rate; water use efficiency; fluorescence and chlorophyll index; foliar area index, incidence of rust and productivity. In conclusion, cultivars Catuaí Amarelo 20/15 cv 479, Araponga MG1 and Tupi 1669-33 presented high response to framework pruning given their high productivity allied to high stomata functionality, photosynthetic rate, water use efficiency and low transpiratory rate. In addition, the two last cultivars presented low incidence of rust. Cultivar Acauã presented good response to this type of pruning for presenting high productivity associated with greater cuticle thickness and lower disease incidence. Cultivar Catuaí Vermelho 785/15 was unresponsive to the framework pruning for presenting lower productivity, high incidence of rust, low vegetative growth and low water use efficiency.